BS IEC 61156-15. Multicore and symmetrical pair/quad cables for digital communications. Part 15. Symmetrical pair/quad cables for horizontal floor wiring with transmission characteristics up to 1 000 MHz and resistance to fire performance characteristics. Sectional specification (26th March 2021) - British Standards Institution,
No abstract available